Clinical Insight into Congenital Hypothyroidism Among Children - Hüseyin Anıl Korkmaz (Children)
Molecular, genetic, and technological advances have led to increased knowledge regarding neonatal thyroid hormone metabolism disorders. Maternal and fetal hypothyroidism, which can cause psychomotor dysfunction syndromes or low IQ levels, can lead to brain damage, reduced fetal growth and incidental fetal death. The treatment of congenital hypothyroidism detected by screening programs performed during the neonatal period provides normalization of growth, IQ levels, and the physical, mental, and motor development of infants. Therefore, the early diagnosis and treatment of congenital hypothyroidism will prevent the development of complications. In this article, the classification and management of neonatal thyroid diseases are reviewed in light of the current scientific literature.